Resource bounded randomness and weakly complete problems - Ambos-Spies, Klaus; Terwijn, Sebastiaan A.; Zheng, Xizhong (Algorithms and computation, 1994)
We introduce and study resource bounded random sets based on Lutz's concept of resource bounded measure ([5, 6]). We concentrate on nc-randomness (c ≥ 2) which corresponds to the polynomial time bounded (p-) measure of Lutz, and which is adequate for studying the internal and quantative structure of E = DTIME(2lin). First we show that the class of nc-random sets has p-measure 1. This provides a new, simplified approach to p-measure 1-results. Next we compare randomness with genericity (in the sense of [1, 2]) and we show that nc+1-random sets are nc-generic, whereas the converse fails. From the former we conclude thatnc-random sets are not p-btt-complete for E. Our technical main results describe the distribution of the nc-random sets under p-m-reducibility. We show that every nc-random set in E has nk-random predecessors in E for any k ≥ 1, whereas the amount of randomness of the successors is bounded. We apply this result to answer a question raised by Lutz [8]: We show that the class of weakly complete sets has measure 1 in E and that there are weakly complete problems which are not p-btt-complete for E.